Role of Asthma Education in the Management of Adult Asthma - Johanne Côté (Canadian Respiratory Journal)
When a patient is newly diagnosed as having asthma, he or she is often prescribed new medication without getting much information on the disease and its treatment. This article emphasizes the need to educate asthmatics. Asthma treatment should begin with a proper adjustment of the medication, allowing asthmatics to lead a normal life. All asthmatics should be shown how to use their inhalation device properly. They should he knowledgeable about the basic aspects of asthma, airway inflammation and bronchoconstriction, use or medication and early symptoms heralding an asthma attack. Environmental factors that may trigger an asthma attack should be explained. Patients should be able to self-monitor asthma using either symptom severity or a peak flow meter. Because asthma is an unpredictable disease, patients should have a self-action plan to implement when their asthma deteriorates.